Morphodynamic Features of Palaeo Ice Streams offshore N-Iceland based on Multibeam Bathymetric and High Resolution Chirp Seismic Data - Höfer, Patricia, 1989- (2019)
Glacial landforms on the N-Iceland shelf associated with the last deglaciation demonstrate that the ice streams of the Last Glacial Maximum extended further north than previously assumed. Multibeam bathymetric data used in this study was acquired during four mapping surveys in 2002-2004. Glacial landforms represent the ice extent of the major ice streams and their associated velocity: Skagafjörður-Skagafjarðargrunn, Eyjafjörður-Eyjafjarðaráll, Bárðardalur-Skjálfandi-Skjálfandadjúp, and Öxarfjörður. Crag and tails, drumlins and high parallelisms of mega-scale glacial lineations not only show the trend of the expected palaeo ice flow, they also show the fast velocity of the ice streams. Asymmetrical ridges interpreted as grounding zone wedges suggest that the deglaciation was episodic, with periods of standstill. A moraine in the northern part of Kolbeinsey Ridge with more than 150 km distance to the present coastline and a 100 km remote grounding zone wedge between Eyjafjarðaráll and Skjálfandadjúp shows a longer extent of Last Glacial Maximum than previously thought. These ice streams extended at least 110 km north of Grímsey during the Last Glacial Maximum. Based on tephrachronological data from sediment cores, the shelf segment from Kolbeinsey to Grímsey was deglaciated before 14000 years b2k (Borrobol or BAS-1 event) and has not been subjected to grounded ice cover since that time. Ummerki ísstrauma ísaldar á landgrunni Norðurlands, kortlagning með fjölgeisla- og hátíðni-endurkastsmælingum. Fjölgeislamælingar sýna að ísstraumar síðustu ísaldar á landgrunni Norðurlands, náðu mun lengra en áður hefur verið talið. Kortlagning hafsbotnsins á þessu svæði á árunum 2002-2004, hefur leitt í ljós markvísleg ummerki meginísstrauma frá Skagafirði út í Skagafjarðardjúp, frá Eyjafirði og út Eyjafjarðarál, frá Bárðardal, Skjálfanda og Öxarfirði út Skjálfandadjúp. Jökulöldur (drumlins, drymbilurðir), skafurðir (crag and tails), og risakembur (mega-scale glacial lineations) endurspegla skriðstefnur og skriðhraða ...